The Relationships between Risky Sexual Practices and Spiritual Intelligence of Adolescents in Indonesia. (29th March 2019) - Simak, Valen Fridolin; Fitriyani, Poppy; Setiawan, Agus
ABSTRACT: Adolescents' health problems are closely related to risky practices, one of which is risky sexual practice. Among others, a factor that is important to prevent risky sexual practices is spiritual intelligence of the adolescents. The study aims to analyze the association between spiritual intelligence and risky sexual practice in adolescents in a junior high school at Curug city of Depok, Indonesia. A quantitative observational analysis with cross-sectional approach was applied. The instrument used to measure the variables of spiritual intelligence was the spiritual intelligence self-report inventory. The variable sexual risky practices was measured with the instrument Sexual Risk Survey (SRS). The study involved 302 adolescents who came from three junior high schools (SMP) selected by stratified random sampling. Pearson test analysis showed a significant negative correlation between spiritual intelligence with sexual risky practices ( p = .019; r = −.135). A multivariate analysis using multiple linear regression showed that sex is the most influential variable on sexual risky practices. Based on the findings of the research, there is a need to continuously monitor the stage of adolescent growth especially by improving the spiritual intelligence status, so that spiritually intelligent adolescents can suppress the incidence of sexual risky practices.